PENERAPAN BLENDED LEARNING BERBASIS GOOGLE CLASSROOM TERHADAP KETERAMPILAN BERPIKIR KREATIF &KEMANDIRIAN BELAJAR PESERTA DIDIK - Muhamad Agustiono; Eeng Ahman; Amir Machmud; Ikaputera Waspada (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
Based on the results of interviews at SMAN 1 Lembang, learning that is usually applied by Economics Subject teachers so far using the expository method is carried out face-to-face in the classroom with the support of adequate facilities and infrastructure, where learning is teacher-centered, passive students, and less involved in learning. This causes students to experience burnout which results in a lack of interest and learning independence. The purpose of this study was to determine the effect of blended learning assisted by google classroom on the creative thinking skills and independent learning of students. This study uses a quantitative approach with a quasi-experimental design. The data collection instrument used an essay test with 15 questions and a questionnaire of 20 questions. The sampling technique of this research was carried out by means of cluster random sampling. Hypothesis testing using independent t-test. The results showed that there was an effect of blended learning assisted by google classroom on students' creative thinking skills and independent learningKeywords: The Perfection of Creative Thinking, Self-Reliance Learning, Blended Learning